2010
DOI: 10.1080/14649055.2010.10766256
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of electronic resource management systems to hiring practices for electronic resources personnel

Abstract: Requirements for electronic resource positions in libraries advertised between the years 2000 and 2008 are reviewed and analyzed according to how they relate to developments in electronic resource management tools and standards taking place during the associated time periods. The research reveals that the job requirements for electronic resource personnel have not changed significantly over these years, despite overwhelming changes in quantity of material and quality of system resources and despite the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Job announcements for ER positions rarely suggest someone with managerial responsibilities. The picture confirms a view of an ER librarian as a “cross between a reference librarian, a collection development officer, acquisitions manager, a cataloger, and an information technology specialist” (Boss & Schmidt, ; quoted in Murdock, , p. 38). Indeed, there is a strong sense of ER librarianship not (yet) having developed as a marked specialty.…”
Section: The Specialtiessupporting
confidence: 52%
See 4 more Smart Citations
“…Job announcements for ER positions rarely suggest someone with managerial responsibilities. The picture confirms a view of an ER librarian as a “cross between a reference librarian, a collection development officer, acquisitions manager, a cataloger, and an information technology specialist” (Boss & Schmidt, ; quoted in Murdock, , p. 38). Indeed, there is a strong sense of ER librarianship not (yet) having developed as a marked specialty.…”
Section: The Specialtiessupporting
confidence: 52%
“…Engel and Robbins's () study suggests that the role is not strongly specialist, but rather one encompassing a wide range of roles. Murdock () found that job adverts continue to expect general competencies in reference and instruction, reinforcing Fisher's () positioning of the role in public services. Sutton's () major study of job advertisements in the United States between 2005 and 2009 showed that professional capabilities such as communication, working collaboratively, and problem solving were the most common attributes listed as actual requirements.…”
Section: The Specialtiesmentioning
confidence: 91%
See 3 more Smart Citations